The influence of indium, gallium and bismuth on the corrosion behavior of alloys intended for protectors - Darko Vuksanović; Časlav Lačnjevac (Zaštita Materijala)
This work was carried out of behavior of Al-Zn alloy systems in chloride solutions of different concentrations, with additional alloying indium, gallium and bismuth as micro alloying elements. In addition to these elements is done by the alloying with tin. Thus obtained aluminum alloy with additional corrosion and electrochemical tests give a chance to produce their own sacrificial electrodes. In preparing the concept on which this paper is based, started from the fact that there are a number of influential factors, starting from the chemical composition, methods of melting, alloying and casting methods that would allow obtaining high-quality alloy that can be effectively used as a protector.